Is there a role of calcitonin gene-related peptide in cortical spreading depression mechanisms?– argument con. - Agustin Melo-Carrillo (The Journal of Headache and Pain)
Abstract Cortical spreading depression (CSD) is a wave of neuronal and glial depolarization followed by suppressed neural activity, thought to underlie migraine aura. While Calcitonin Gene-Related Peptide (CGRP) is well established in migraine pathophysiology, its role in CSD remains uncertain. This comment evaluates evidence suggesting that CGRP is not directly involved in CSD initiation or propagation but may contribute to nociceptive activation associated with migraine. While some studies report CGRP-related effects on CSD susceptibility, methodological limitations raise concerns about their interpretation. Electrophysiological data indicate that CGRP does not influence the ionic mechanisms driving CSD. However, CGRP plays a key role in sensitizing nociceptive neurons, and CGRP-targeting drugs effectively modulate migraine pain without altering CSD dynamics. Clinical findings further suggest that peripheral CGRP inhibition reduces headache burden, potentially allowing the brain to recover from chronic pain states. In conclusion, while CGRP is integral to migraine pain modulation, its direct involvement in CSD appears minimal, highlighting distinct pathways for aura and headache pathophysiology.